Literacy as Power and Its Impacts on Women’s Empowerment in Kathryn Stockett’s The Help - Faradilla Khairin Nisa'; Much. Koiri (Journal of English Language and Education, 2026)
This study reveals how literacy functions as a form of power and shapes women’s empowerment in Kathryn Stockett’s novel, The Help (2009). Drawing on New Literacy Studies, Williams and Zenger’s (2007) concept of literacy as power, and Kabeer’s (1999) empowerment framework, it employs qualitative textual analysis of three key literacy events: the book’s initiation, the writing process, and its publication. The findings show that literacy operates through control over meaning, action production, and strategicity, enabling marginalized Black women to challenge dominant racial narratives, navigate risk, and generate social consequences. Within Kabeer’s framework, literacy emerges as a strategic resource that enables agency and produces achievements, including economic mobility and psychological autonomy. Rather than merely a medium of expression, literacy is shown to function as a socially embedded and strategic practice through which marginalized women negotiate and reshape power relations.